Phylogenetic and Kinetic Diversity of Aerobic Vinyl Chloride-Assimilating Bacteria from Contaminated Sites - Coleman, Nicholas V. (American Society for Microbiology, 2002)
Aerobic bacteria that grow on vinyl chloride (VC) have been isolated previously, but their diversity and distribution are largely unknown. It is also unclear whether such bacteria contribute to the natural attenuation of VC at chlorinated-ethene-contaminated sites. We detected aerobic VC biodegradation in 23 of 37 microcosms and enrichments inoculated with samples from various sites. Twelve different bacteria (11 Mycobacterium strains and 1 Nocardioides strain) capable of growth on VC as the sole carbon source were isolated, and 5 representative strains were examined further. All the isolates grew on ethene in addition to VC and contained VC-inducible ethene monooxygenase activity. The Mycobacterium strains (JS60, JS61, JS616, and JS617) all had similar growth yields (5.4 to 6.6 g of protein/mol), maximum specific growth rates (0.17 to 0.23 day(−1)), and maximum specific substrate utilization rates (9 to 16 nmol/min/mg of protein) with VC. The Nocardioides strain (JS614) had a higher growth yield (10.3 g of protein/mol), growth rate (0.71 day(−1)), and substrate utilization rate (43 nmol/min/mg of protein) with VC but was much more sensitive to VC starvation. Half-velocity constant (K(s)) values for VC were between 0.5 and 3.2 μM, while K(s) values for oxygen ranged from 0.03 to 0.3 mg/liter. Our results indicate that aerobic VC-degrading microorganisms (predominantly Mycobacterium strains) are widely distributed at sites contaminated with chlorinated solvents and are likely to be responsible for the natural attenuation of VC.